2011
DOI: 10.1128/jb.05301-11
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Escherichia coli UmuC Active-Site Loops Identifies Variants That Confer UV Hypersensitivity

Abstract: DNA is constantly exposed to chemical and environmental mutagens, causing lesions that can stall replication. In order to deal with DNA damage and other stresses, Escherichia coli utilizes the SOS response, which regulates the expression of at least 57 genes, including umuDC. The gene products of umuDC, UmuC and the cleaved form of UmuD, UmuD, form the specialized E. coli Y-family DNA polymerase UmuD 2 C, or polymerase V (Pol V). Y-family DNA polymerases are characterized by their specialized ability to copy d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 79 publications
4
19
0
Order By: Relevance
“…It is possible that DinB(C66A) may sequester free UmuD from the cellular pool, which would mimic a deletion of the umuDC operon, previously shown to enhance homologous recombination (15,45,55,56). Thus, if increased MPC formation mediated by DinB(C66A) effectively decreases the concentration of free UmuD, then the increase in homologous recombination is consistent with previous findings (15,45,47). Another possibility is that the increased concentration of DinB MPCs directly enhances recombination.…”
Section: Figsupporting
confidence: 83%
See 1 more Smart Citation
“…It is possible that DinB(C66A) may sequester free UmuD from the cellular pool, which would mimic a deletion of the umuDC operon, previously shown to enhance homologous recombination (15,45,55,56). Thus, if increased MPC formation mediated by DinB(C66A) effectively decreases the concentration of free UmuD, then the increase in homologous recombination is consistent with previous findings (15,45,47). Another possibility is that the increased concentration of DinB MPCs directly enhances recombination.…”
Section: Figsupporting
confidence: 83%
“…We then examined the ability of the dinB(C66A) strain to undergo homologous recombination, which is largely mediated by RecA but is affected by the activities of TLS polymerases (15,45,46). To this end, we employed a P1 transduction assay, which has previously been shown to be effective in quantification of recombination events (47). In this assay, the number of transductants directly correlates with the number of recombination events.…”
Section: (A) Sds-page Of Elution Fractions For Hexahistidine-tagged Dmentioning
confidence: 99%
“…Cryo-electron microscopy shows that pol V binds to the end as well as within the grooves of the RecA-ssDNA nucleoprotein filament [25]. Our previous work suggested that a possible binding site for RecA on UmuC could be UmuC residues 32 through 34 [26], which was subsequently predicted via molecular modeling [27].…”
Section: Introductionmentioning
confidence: 93%
“…Strain AB1157 dinB harboring UmuC variants identified in the selection process and re-constructed in fresh plasmids as explained in Section 2.2 (Table 2) was exposed to increasing concentrations of NFZ as described previously [26,49,63]. Serial dilutions (20-fold) of overnight cultures were plated on LB agar plates containing 60 g/mL spectinomycin and the indicated amount of NFZ.…”
Section: Nfz Survival Assaysmentioning
confidence: 99%
See 1 more Smart Citation